2ln(x+9)-8lnx=

Simple and best practice solution for 2ln(x+9)-8lnx= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2ln(x+9)-8lnx= equation:


Simplifying
2ln(x + 9) + -8lnx = 0

Reorder the terms:
2ln(9 + x) + -8lnx = 0
(9 * 2ln + x * 2ln) + -8lnx = 0
(18ln + 2lnx) + -8lnx = 0

Combine like terms: 2lnx + -8lnx = -6lnx
18ln + -6lnx = 0

Solving
18ln + -6lnx = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '6ln'.
6ln(3 + -1x) = 0

Ignore the factor 6.

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing l to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Add 'x' to each side of the equation. -1x + x = -3 + x Combine like terms: -1x + x = 0 0 = -3 + x Simplifying 0 = -3 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| lne^3x= | | 9(2y-9)-(8y+5)= | | 13+18x=535 | | 12+20x=132 | | (5x+1)(4x^2+2x+3)= | | 3t=-2 | | 7x^4-63x^2=0 | | 8b-6a-5a+6b= | | 3x^3=12 | | 4r=4 | | 18x^2=6x^4 | | 9p+7p+6p= | | 2x+15x= | | 59-7x=20x+17 | | x=14-8 | | 6(r-3)-2(r+5)+10= | | 56-3x=10x+17 | | p-7=9 | | 92-2x=43x+17 | | 2x^3+x^2+13x+84=0 | | 2x-4=10x-64 | | 112r^3+34r^2-6r=0 | | -4x-7y=5 | | 4(2u-3)=44 | | 2*6+{7*8}-67= | | 6a^2+13a=5 | | 18a^3b-39a^2b-15ab=0 | | -4-5x=8-8x | | 8(t-2)+6t=7(2t+2)-10 | | 6.3+.5x=16.3 | | 120-8-8-8= | | -[6x+(4x+3)]=7-(5x+6) |

Equations solver categories